Coffee Purchase Decision: Price, Communication, and Shop Image Influence: Pengaruh Harga, Komunikasi Pemasaran, dan Citra Toko terhadap Keputusan Pembelian Kopi - Ircham Arief Ramadhan; Misti Hariasih (Academia Open, 2023)
This study aimed to investigate the impact of price, marketing communication, and shop image on coffee purchase decisions at Warung WAKU "Warung Ku." A quantitative approach was adopted, utilizing questionnaire data collected from 100 respondents. Non-probability sampling, specifically incidental sampling, was employed to select the participants. The validity, reliability, classical assumptions, multiple linear regression, partial tests, simultaneous tests, multiple correlation coefficient tests, and multiple determination tests were conducted to analyze the data. The results of the simultaneous test indicated that price, marketing communication, and shop image collectively exerted a significant influence on coffee purchasing decisions. Moreover, the partial test revealed that price, marketing communication, and shop image individually impacted coffee purchasing decisions at WAKU "warung ku" stalls, with shop image displaying a particularly significant effect. This research provides valuable insights into the factors influencing consumers' coffee purchase decisions and offers implications for marketers and practitioners to enhance their strategies and overall performance in the competitive coffee industry. Highlights: The study examines the influence of price, marketing communication, and shop image on coffee purchase decisions. Quantitative analysis and questionnaire data from 100 respondents were utilized to determine the impact of these factors. The results highlight the significant role of shop image and provide insights for marketers to enhance their strategies in the competitive coffee industry. Keywords: Coffee purchase decision, Price, Marketing communication, Shop image, Quantitative analysis.